Scientific Approaches to the Philosophy of Religion
X, 280 p.
Keywords: Tackling central problems in philosophy of religion by referring to relevant theories and findings in cognitive science, anthropology, developmental psychology, decision theory, biology, physics, cosmology, the contributors address a range of topics, including divine attributes; God, creation and evolution; God and the universe; religious beliefs.